Humanitarian resistance in the context of digitalisation of education - I. Ya. Murzina (Obrazovanie i Nauka)
Introduction. In the context of a pandemic, significant transformations in education have occurred: the urgent shift to new forms of learning and digitalisation of the learning process have become a challenge to the traditional understanding of education as a public good, based on humanistic grounds. In the media and social networks, there was a public debate over the prospects of the education for several months. The disparity in opinions and not always accurate determination of the positions of the authors of numerous publications highlight the need for analysing the situation in modern education from the standpoint of axiology and cultural studies.Aim. The present publication is aimed to consider the current changes in education in the conditions of digitalisation and to identify the potential of humanistic pedagogy.Methodology and research methods. The study is based on an interdisciplinary methodology, which integrates the achievements of the humanities and social sciences. The method of cluster analysis, content analysis in the mass media and social media, supplemented by group identification analysis, were employed.Research results. According to the findings of the present study, it was concluded that the contemporary processes in Russian education can be described from the point of view of trauma theory. The author introduces the concept of “humanitarian resistance”, which is referred to the forms of symbolic protest, based on the values of humanism, national and cultural traditions, and non-violence. Furthermore, the author proposes a primary classification of the forms of humanitarian resistance in Russian education, including worldview, axiological, socio-psychological and pedagogical aspects. In the current article, the essence of each aspect is disclosed on specific examples.Scientific novelty of the conducted research lies in the theoretical justification of the analysis of current educational practices from a philosophical and cultural point of view. The introduction of new categories into scientific circulation allows for an adequate description of the current processes in education. The article is debatable, involving the discussion on the problems of education as a public good and the teacher as a bearer of the humanistic tradition in terms of digitalisation.Practical significance of the research consists in the possibility of using its results to determine the prospects of educational policy in the digital society, as well as to develop the strategies and to select teacher training routes in new conditions.